Get Rich Syndrome: Examining the Fight against Cybercrime in Enugu State, Nigeria - Idemili-Aronu, Ngozi; Ajah, Ifeyinwa Angela; Ezeanya, Oguejiofo C. P.; Omaliko, Joy Chikaodili; Nwonovo, Oluchukwu Sunday (International Journal of Criminology and Sociology, 2021)
Despite the large scale provisions within the Nigerian legal framework that address the issue of cyber frauds, there is an alarming increase in cyber-offences in Nigeria. This necessitated the present study that employed semi-structured interviews to draw data from civil servants from grade level twelve and above and business owners aged 40 years and over [N = 34]. The study participants were recruited through a purposive sampling method and data were analyzed thematically. Results show that individuals and different organizations are often hit through direct hacking, malware planting, and many other more sophisticated means by cyber-criminals. The study calls for the Nigerian leaders to reach a consensus on the meaning of cyber fraud, the effects and roles each community must play to reach an agreed goal. Parents need to also balance euphoria in their children with training and preparations for the harsh environments in the real world.